2017
DOI: 10.3389/fpls.2017.00285
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Small RNAs in Phosphorus and Sulfur Sensing, Signaling and Stress: Current Update

Abstract: Plants require several essential mineral nutrients for their growth and development. These nutrients are required to maintain physiological processes and structural integrity in plants. The root architecture has evolved to absorb nutrients from soil and transport them to other parts of the plant. Nutrient deficiency affects several physiological and biological processes in plants and leads to reduction in crop productivity and yield. To compensate this adversity, plants have developed adaptive mechanisms to en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 145 publications
1
21
0
Order By: Relevance
“…The P leaf concentration of the mutant pho1 is very diminished while in the roots it has concentrations very similar to those of the wild cultivar, which suggests that this mutant has a defect in the loading of P into the xylem [100,[102][103][104]. By contrast, the pho2 mutant accumulates up to three times more P in the aerial part than the wild cultivar, while the root maintains similar levels, or even slightly lower levels than the wild cultivar [43,101,105,106]. The pho2 mutant could either prevent the transport of P through the phloem, from the aerial part to the root, or have some problem in the regulation of P concentration in the leaves [107].…”
Section: Hormones and Signaling Substances In The Regulation Of Fe Anmentioning
confidence: 88%
See 3 more Smart Citations
“…The P leaf concentration of the mutant pho1 is very diminished while in the roots it has concentrations very similar to those of the wild cultivar, which suggests that this mutant has a defect in the loading of P into the xylem [100,[102][103][104]. By contrast, the pho2 mutant accumulates up to three times more P in the aerial part than the wild cultivar, while the root maintains similar levels, or even slightly lower levels than the wild cultivar [43,101,105,106]. The pho2 mutant could either prevent the transport of P through the phloem, from the aerial part to the root, or have some problem in the regulation of P concentration in the leaves [107].…”
Section: Hormones and Signaling Substances In The Regulation Of Fe Anmentioning
confidence: 88%
“…The pho2 mutant could either prevent the transport of P through the phloem, from the aerial part to the root, or have some problem in the regulation of P concentration in the leaves [107]. More recently, it has been shown that the pho2 mutant lacks a E2 enzyme, which is involved in ubiquitination processes and signaling against P deficiency [104,106]. PHO2 is involved in the degradation of PHO1 via a ubiquitination pathway [106,108].…”
Section: Hormones and Signaling Substances In The Regulation Of Fe Anmentioning
confidence: 99%
See 2 more Smart Citations
“…MicroRNAs (miRNAs) are 21 to 24 nt-long endogenous non-coding RNAs that widely mediate growth, development, and adaptive response to abiotic stresses via regulating target genes at the posttranscriptional or translation level ( Bonnet et al, 2006 ; Mallory and Vaucheret, 2006 ; Sunkar et al, 2012 ; Ci et al, 2015 ; Sun et al, 2015 ). Numerous miRNA families identified have been confirmed to impact on plant responses to nutrient deprivation and salt stress ( Jones-Rhoades and Bartel, 2004 ; Fujii et al, 2005 ; Chiou et al, 2006 ; Yamasaki et al, 2007 ; Liang et al, 2010 ; Barciszewska-Pacak et al, 2015 ; Khaksefidi et al, 2015 ; Kumar et al, 2017 ). Upon Pi starvation, miR156, miR399, miR778, miR827, and miR2211 of Arabidopsis ( Arabidopsis thaliana ) display an upregulated expression pattern ( Fujii et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%